IMPROVING INNOVATION COMPETENCE OF EDUCATORS- PSYCHOLOGISTS IN CONTINUOUS EDUCATION SYSTEM - Azizova Kyzlarkhan Mashrabovna (Zeta Repository, 2023)
The article discusses the essence of managing the formation of innovative competence of pedagogues-psychologists in the innovative field of continuous education. Its structure and ways to create educational modernization projects and programs for its implementation are shown.